Correlates of recent overdose among people who inject drugs in the San Diego/Tijuana border region. (1st November 2022) - Bailey, Katie; Abramovitz, Daniela; Patterson, Thomas L.; Harvey-Vera, Alicia Y.; Vera, Carlos F.; Rangel, Maria Gudelia; Friedman, Joseph; Davidson, Peter; Bourgois, Philippe; Strathdee, Steffanie A.
Abstract: Background: Along the Mexico-US border, illicitly manufactured fentanyls (fentanyl) have been detected in other illicit drugs, including street opioid formulations known as 'china white.' We studied correlates of recent overdose among people who inject drugs (PWID), focusing on the risk of knowlingly or unknowingly using fentanyl in china white. Methods: From October 2020 - September, 2021 we surveyed participants in San Diego, California and Tijuana, Mexico and employed Poisson regression to identify correlates of recent overdose. Results: Of 612 PWID, most were male (74.0 %), Latinx (71.9 %), US residents (67.0 %). Mean age was 43 years. In the last six months, 15.8 % experienced overdose, 31.0 % knowingly used fentanyl and 11.1 % used china white, of whom 77.9 % did not think it contained fentanyl. After controlling for sex and race, factors independently associated with risk of overdose included knowingly using fentanyl, using china white and not believing it contained fentanyl, recent drug rehabilitation, being stopped/arrested by police, and homelessness. Further, PWID who believed china white contained fentanyl were less likely to use it. Conclusions: Both intentional fentanyl use and unintentional exposure to fentanyl via china white were associated with overdose risk; however, PWID who believed china white contained fentanyl were less likely to use it. These data suggest that advanced drug checking systems should be implemented to empower PWID to avoid dangerous street formulations or to plan their drug use knowing its contents. Other overdose risk factors such as decreased tolerance following drug treatment, police interactions, and homelessness also require urgent intervention. Highlights: Fentanyl is commonly found in heroin and other illicit drugs in North America. Overdose was associated with use of powder heroin known as china white. Most who used china white did not believe it contained fentanyl. Those who believed china white contained fentanyl were less likely to use it. Harm reduction measures like drug checking may help people avoid overdose.